2019
DOI: 10.3390/joitmc5020034
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Personal Value on CSV (Creating Shared Value)

Abstract: The purpose of this study is to reveal the effect of personal value as a part of creating shared value (CSV). We extracted factors of personal value through a literature review. Personal value consists of social commitment, self-actualization, goal setting, and solidarity. Self-actualization is the universal motivation of the individual, goal setting is the basis for the occurrence of action, and solidarity is the relationship factor that defends competition and personalization. This study was conducted on thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Board members were not faithful to their roles, and members did not participate in the cooperative's economic and organizational activities. Social engagement is influenced by goal setting, such as sharing common goals, participation, and leadership, and can be strengthened by relationships, cooperation, and solidarity [28]. KOPABUGI established bylaws on common goals and members' responsibility, but set neither specific short-and long-term goals to achieve them nor plans for members' participation and role division.…”
Section: Comparison Of Kopabugi and Codaricamentioning
confidence: 99%
“…Board members were not faithful to their roles, and members did not participate in the cooperative's economic and organizational activities. Social engagement is influenced by goal setting, such as sharing common goals, participation, and leadership, and can be strengthened by relationships, cooperation, and solidarity [28]. KOPABUGI established bylaws on common goals and members' responsibility, but set neither specific short-and long-term goals to achieve them nor plans for members' participation and role division.…”
Section: Comparison Of Kopabugi and Codaricamentioning
confidence: 99%
“…Kang and Na (2020) confirmed that the social value and environmental value of corporate CSV have a positive effect on enterprise image and suggested a strategic direction for enhancing enterprise image through corporate CSV activities. Koo et al (2019) proved the positive influence relationship between social value and corporate leadership of CSV. In the study by Jin (2018), CSV activity had positive effects on enterprise image.…”
Section: Relationship Between Csv and Enterprise Imagementioning
confidence: 91%
“…In this study, CSV is defined as a management strategy for balanced and inclusive social development through the sharing of stakeholder values related to a company and the fair allocation of CSV as economic, social and cooperative values (Jin, 2018; Koo et al. , 2019; Kouatli, 2019; Kramer and Porter, 2011; Moon and Parc, 2019).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations